Counter-terrorism strategy between Indonesia and Malaysia: a study on Jemaah Islamiyyah threats / Robi Nurhadi - Nurhadi, Robi (2014)
The main purpose of this study is to compare the counter-terrorism strategies adopted by the Indonesian and Malaysian government against the threats of Jemaah Islamiyah (JI). This study also analyzes the effects of the democratization process in the two countries towards the implementation of counter terrorism strategy. The results indicate that there are some differences in the counter-terrorism approaches applied by the two countries. Malaysia more emphasizes on the preemptive side of the counter terrorism approaches, while Indonesia accentuates on the curative-legalistic aspect. Moreover, the counter-terrorism strategies of the two countries have also been affected by two factors: (i) political factors which occurred in both countries; (3) different counter-terrorism approaches factors. This study proves that the handling of the threats of terrorism, not just employ a security approach alone, but must also utilize other approaches. The existence of democratization factor in the case of Indonesia and Malaysia should be require in the counter-terrorism strategy. The study is significant since it contributes to more systematic understanding on counter terrorism approaches and strategies by two major Muslim-majority countries in the region.